2019
DOI: 10.1002/cam4.1788
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and efficiency of concurrent chemoradiotherapy with a single agent or double agents vs radiotherapy alone for elderly patients with esophageal squamous cell carcinoma: Experience of two centers

Abstract: The incidence of elderly patients with esophageal cancer (OC) is increasing as the population ages. Until now, the treatment strategy in these patients has been unclear. The aim of our study was to assess the efficiency and tolerance of treatment with radiotherapy alone (RT alone), single‐agent‐based concurrent chemoradiotherapy (CCRT‐1), or double‐agent‐based concurrent chemoradiotherapy (CCRT‐2) in elderly patients (≥65 years) with OC. A total of 271 patients with OC aged 65 years or older were included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
2
15
1
Order By: Relevance
“…Huang et al . reported that the rate of grade ≥3 toxicities was 25.5% among 271 elderly EC patients who received concurrent chemoradiotherapy ( 21 ). Zhao et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al . reported that the rate of grade ≥3 toxicities was 25.5% among 271 elderly EC patients who received concurrent chemoradiotherapy ( 21 ). Zhao et al .…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al . reported an MST of 23.6 months and a median PFS of 13.6 months among 271 elderly patients ( 21 ). Zhao et al .…”
Section: Discussionmentioning
confidence: 99%
“…RT alone should be recommended with caution even in the eldest group (aged > 85 years). If patients cannot tolerate doublet CT combined with RT, single-drug oral CT drugs can be considered, such as S1, Xeloda, and other uorouracil analogues [12,35].…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing concurrent chemoradiation with single agent versus multi agent chemotherapy have also suggested that single-agent chemoradiation are not inferior to multi-agent treatment in terms of outcomes, and are better tolerated with good toxicity profiles [18][19]. Again these are retrospective, institutional experiences.…”
Section: Discussionmentioning
confidence: 99%